Adipose Tissue Hypoxia, Inflammation, and Fibrosis in Obese Insulin-Sensitive and Obese Insulin-Resistant Subjects - Lawler, Helen M. (J Clin Endocrinol Metab, 2016)
CONTEXT: A substantial number of obese individuals are relatively insulin sensitive and the etiology for this variation remains unknown. OBJECTIVE: The primary objective was to detect factors in adipose tissue differentiating obese insulin-sensitive (OBIS) from obese insulin-resistant (OBIR) individuals and investigate whether adipose tissue hypoxia is a contributing factor in the pathogenesis of insulin resistance. DESIGN AND SETTING: This was a cross-sectional study in the general community. PARTICIPANTS: Subjects consisted of nondiabetic OBIS and OBIR subjects with similar body mass index, age, and total body fat but different insulin sensitivity index as well as lean insulin-sensitive subjects. INTERVENTION(S): There were no interventions. MAIN OUTCOME MEASURE(S): We examined adipocytokines and the expression of candidate genes regulating hypoxia, inflammation, and lipogenesis in adipose tissue and adipose tissue oxygenation. RESULTS: OBIS subjects had increased plasma adiponectin but similar plasma TNFα and leptin levels as compared with OBIR subjects. Genes regulating inflammation (CD68, MCP1, scavenger receptor A, and oxidized LDL receptor 1) were increased by 40%–60% (P < .05) in OBIR vs OBIS cohorts. In addition, genes involved in extracellular matrix formation such as collagen VI and MMP7 were up-regulated by 43% and 78% (P < .05), respectively, in OBIR vs OBIS. The expression of HIF1α and VEGF gene expression was increased by 37% and 52%, respectively, in OBIR vs OBIS (P < .01). Despite the differential expression in hypoxia-related genes, adipose tissue oxygenation measured by a Licox oxygen probe was not different between OBIS and OBIR subjects, but it was higher in lean subjects as compared with obese subjects. CONCLUSIONS: We confirmed that adipose tissue inflammation and fibrosis play an important role in the pathogenesis of insulin resistance independent of obesity in humans. Whether hypoxia is simply a consequence of adipose tissue expansion or is related to the pathogenesis of obesity-induced insulin resistance is yet to be understood.